Towards noise engineering: recent insights in low-frequency excess flux noise of superconducting quantum devices - Kempf, Sebastian; Ferring-Siebert, Anna; Enss, Christian (Applied physics letters, 2016)
The comprehensive analysis of low-frequency excess flux noise both in terms of magnetic flux noise SΦ,1/f and energy sensitivity ϵ1∕f of 84 superconducting quantum devices studied at temperatures below 1 K reveals a universal behavior. When analyzing data in terms of ϵ1∕f, we find that noise spectra of independent devices cross each other all at certain crossing frequencies fc. Besides this main result of our paper, we further show that superconducting quantum interference device (SQUID) arrays systematically feature higher noise exponents than single SQUIDs and give evidence for a material and device type dependence of low-frequency excess flux noise. The latter results facilitate to engineer the shape of magnetic flux noise spectra and thus to experimentally modify key properties such as coherence or measurement times of superconducting quantum devices.
Gesehen am 11.05.2020